18th International Conference on Nuclear Engineering: Volume 2 2010
DOI: 10.1115/icone18-30212
|View full text |Cite
|
Sign up to set email alerts
|

Development of Buildup Factors for Updating the ANSI/ANS-6.4.3 Standard

Abstract: The ANSI/ANS-6.4.3-1991 Standard, Gamma-Ray Attenuation Coefficients and Buildup Factors for Engineering Materials, is currently being updated by an American Nuclear Society (ANS) Working Group. The ANSI/ANS-6.4.3, 1991 standard, which is “withdrawn” due to the failure to meet the requirement of the ANS to have standards updated every ten years, contains buildup factor values that are derived from data that is over seventeen years old. In addition, computer technology has significantly improved since 1991, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It can be observed that the majority of results of this work has a difference lower than 10%, which is a good limit in this regard, as mentioned in [6,[28][29][30]. The differences occurred because of different calculation methods (moments method versus Monte Carlo method), different Monte Carlo models and different cross-section data libraries.…”
Section: Jinst 15 P05018 3 Results and Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It can be observed that the majority of results of this work has a difference lower than 10%, which is a good limit in this regard, as mentioned in [6,[28][29][30]. The differences occurred because of different calculation methods (moments method versus Monte Carlo method), different Monte Carlo models and different cross-section data libraries.…”
Section: Jinst 15 P05018 3 Results and Discussionmentioning
confidence: 65%
“…The BF values for soft tissue (ICRU-44) and A-150 tissue equivalent plastic up to 10 mfp determined in this paper using MCNP. 30. ± 0.02 3.32 ± 0.02 7.39 ± 0.09 7.43 ± 0.09 23.50 ± 0.60 23.92 ± 0.61 66.35 ± 2.18 80.59 ± 2.98 238.18 ± 7.85 257.56 ± 6.73 0.5 2.56 ± 0.02 2.56 ± 0.02 5.07 ± 0.06 5.10 ± 0.06 12.87 ± 0.33 13.01 ± 0.33 34.42 ± 1.28 ± 1.20 ± 3.09 59.19 ± 3.21 1 2.08 ± 0.01 2.09 ± 0.01 3.59 ± 0.04 3.60 ± 0.04 7.27 ± 0.19 7.57 ± 0.2 14.18 ± 0.58 13.98 ± 0.67 24.47 ± 1.21 22.05 ± 1.11 2 1.73 ± 0.01 1.73 ± 0.01 2.58 ± 0.03 2.58 ± 0.03 4.38 ± 0.12 4.45 ± 0.11 7.45 ± 0.31 7.40 ± 0.30 13.42 ± 0.67 11.41 ± 0.57…”
mentioning
confidence: 99%
“…A comprehensive data set (ANSI/ANS-6.4.3) of the exposure buildup factors up to depths of 40 mfp was further developed in 1991 [4] but was withdrawn in 2001. However, a revision of the ANSI/ANS-6.4.3 standard is in development [5,6]. Of course, between 2002 and 2004, calculation of the exposure buildup factors up to 100 mfp were carried out [7][8][9].…”
Section: Introductionmentioning
confidence: 99%